PENGARUH KEPEMIMPINAN TERHADAP MOTIVASI KINERJA PETUGAS LEMBAGA PEASYARAKATAN - Irpan Ariyansyah; Mitro Subroto (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
Performance is the result of work produced by employees in accordance with their role in the organization. Employee performance is one of the most important things in an organization to achieve goals so that various efforts must be made by the organization to improve it. This study aims to analyze the effect of leadership and employee empowerment on work motivation and employee performance. The data and sources used are the results of previous research. Furthermore, the data that has been collected was analyzed using descriptive methods. The results of this study conclude that leadership has a significant effect on work motivation